Nursing interventions concerning the bonding of hospitalized newborns – scoping review - Querido, Débora (2022)
Introduction: The bonding process consists of an emotional bond between the newborn and the parents or caregiver. The newborn's attachment to his caregiver is the basis of all subsequent relationships that he will develop throughout life. Objective: To map nursing interventions that promote bonding in newborns in need of hospitalization. Method: This scoping review was carried out according to the method of the Joanna Briggs Institute, the main sources of information being the databases: PubMed, MEDLINE, CINAHL via EBSCO, LILACS, Cochrane Library, Academic Search Complete, in portuguese and english, without time limit. Results: 53 studies were included in this review. The nursing interventions identified in the literature are divided into two groups: in promoting interaction between parents and the newborn, namely physical proximity, the promotion of breastfeeding, the inclusion of parents in the care of the newborn, and in interaction between parents and the nursing team, through communication and emotional support. Conclusion: Nurses play a fundamental role in reestablishing the binding process between the hospitalized newborn and the parents, so that they are able to move from a role in which they are mere spectators to become the main caregivers of the newborn, trained and linked.